FILSAFAT TARI DALAM KEBUDAYAAN BALI - Ni Made Pira Erawati (Widyadari, 2024)
Balinese dance is an ethnic Balinese dance that is imbued with Balinese Hindu cultural values, as an embodiment of Balinese cultural character. The characteristics of Balinese culture are socio-religious which contains its own philosophy which can be categorized as sacred art and profane art. With the categories sacred and profane, Balinese dance is classified into wali, bebali and balih-balihan arts. As a sacred art, Balinese dance is a treat of beauty to the forces of nature, and as a profane art, it is a treat of beauty to society. This article aims to understand the philosophy of dance in relation to Balinese culture which is based on Hindu religious teachings. The problem that is the main subject of the study to explain this goal is, what is meant by Balinese dance, and what is its relationship with Balinese culture. The study of the problems above is based on the results of observations of Balinese dance which were analyzed using the approach of art philosophy and aesthetic theory which is divided into morphological aesthetics and psychological aesthetics. The results of this study show that Balinese dance contains a philosophy of life that is imbued with the teachings of Balinese Hinduism in realizing truth and purity aesthetically